GENDER AND NEW URBAN AGENDA IN THE CITY OF MADRID (Perspectivas de las Ciencias Económicas y Jurídicas, 2022)
The general objective of this research was to identify the articulation strategies between the National and Local Governments for the implementation of public policies for the development of article 31 of the Ley Orgánica 3/2007 para la Igualdad Efectiva de Mujeres y Hombres. They were specific objectives, namely: a) determine the content of Sustainable Development Goals 5 and 11 from the legal dimension and the rights approach; b) analyze the relationships between Sustainable Development Goals 5 and 11 by analyzing the Right to the City from a gender perspective; and c) survey and delimit the content of the legal instruments of the Spanish legal system in general and of the Madrid legal system in particular in the area of urban policies and gender. The methodology used was qualitative and consisted of the use of content analysis to address legal norms, judicial decisions and public policy instruments, and in-depth interviews to account for the specific role of the Madrid City Council's Espacios de Igualdad. It was concluded that Spain does not expressly recognize the right to the city as a human right in its legal system, although it has been taken as the basis of the Agenda Urbana Española 2019, a non-normative instrument that, based on the 2030 Agenda, is intended to be a guide for local public policies on the matter that, in addition, recognizes the need to repair the situation of women. Likewise, the Superior Court of Justice of Madrid has made use of the notion of Henri Lefebvre to provide the basis for its decisions on gender and urban planning. In article 31 of Law 31/2007 on Igualdad Efectiva entre Mujeres y Hombres, some rights related to the right to the city of women are protected, but it is not fully incorporated. In addition, in its purpose of “making city”, the Madrid City Council lacks an ordered regulatory subsystem in terms of urban planning, consisting of predominantly technical standards of a dispersed nature and with a criterion of the exclusive public space with respect to disadvantaged groups.
Keywords: GENDER; ECONOMIC SOCIAL CULTURAL AND ENVIRONMENTAL RIGHTS; RIGHT TO THE CITY; NEW URBAN AGENDA; PUBLIC POLICY